Automatic control of mechatronic systems - Schlacher, Kurt; Kugi, Andreas (Zielona Góra: Uniwersytet Zielonogórski)
This contribution deals with different concepts of nonlinear control for mechatronic systems. Since most physical systems are nonlinear in nature, it is quite obvious that an improvement in the performance of the closed loop can often be achieved only by means of control techniques that take the essential nonlinearities into consideration. Nevertheless, it can be observed that industry often hesitates to implement these nonlinear controllers, despite all advantages existing from the theoretical point of view.
Keywords: mechatronic systems; differential geometry; passivity; input/output linearization